2010
DOI: 10.1177/0267659110387846
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cerebral tissue and central venous oxygen saturation during off-pump coronary bypass graft surgery

Abstract: We compared simultaneous regional cerebral oxygen saturation and central venous oxygen saturation at different time periods in 20 adult patients (median age, 57.9; range, 35 to 76 years) undergoing off-pump coronary artery bypass (OPCAB) graft surgery (n= 20). Mean arterial pressure (MAP), partial pressure of carbon dioxide (PcvCO(2)), heart rate, haematocrit (Hct), lactate and patient oxygen saturation (SpO(2)) were also recorded as a secondary analysis to determine independent predictors of cerebral desatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Partial pressure of carbon dioxide (PaCO 2 ) was identified as a major predictor of cerebral saturation 24 since it was found to be the most potent physiologic cerebral vasodilator with the rate of cerebral blood flow increases linearly by 2-4% per mm Hg PaCO 2 within the range of 25-75 mm Hg. 25 , 26 There were no significant differences in our study between both groups in ETCO 2 since we maintained ETCO 2 within the normal range by mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Partial pressure of carbon dioxide (PaCO 2 ) was identified as a major predictor of cerebral saturation 24 since it was found to be the most potent physiologic cerebral vasodilator with the rate of cerebral blood flow increases linearly by 2-4% per mm Hg PaCO 2 within the range of 25-75 mm Hg. 25 , 26 There were no significant differences in our study between both groups in ETCO 2 since we maintained ETCO 2 within the normal range by mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…The study further stated that with every one unit increase in left cerebral oxygen saturation, there was a corresponding 0.760 unit increase in ScvO 2 And with every one unit increase in right cerebral oxygen saturation, there was a corresponding 0.879 unit increase in ScvO 2 . 15 McQuillen et al, study on the association between regional and ScvO 2 in pediatric cardiac surgery concluded that neither individual values, nor changes in rSO2 are interchangeable measures of ScvO2 in postoperative pediatric cardiac patients. 16 Coronary artery disease is a disease of the adult population, and cardiac surgery in pediatric population was not considered in the current study.…”
Section: Discussionmentioning
confidence: 99%